Evaluating the impact of Fourth Industrial Revolution on Education in the rural areas in South Africa - Chavalala, Miehleketo (University of the Witwatersrand, Johannesburg, 2021)
The purpose of this research study is to evaluate the impact of Fourth Industrial Revolution (4IR) on education in rural areas in South Africa. This research investigates the following objectives, which are: the impact of 4IR technologies on education and how these technologies can improve the education system in primary and secondary schools in South Africa; the quality of education system in South Africa and factors contributing to the poor education system; how to bridge the gap between the marginalised communities, rural public schools, and urban private schools. The study is focused on public schools in the rural areas in South Africa. Qualitative research strategy has been applied in this research study, interviews have been conducted to afford the researcher an opportunity to interact with stakeholders from the education sector and telecommunication industry. The sample and targeted population of the interviewees are educators from rural schools, former students from rural schools who are in the ICT sector, educators from higher education and 4IR committee member(s). The research strategy applied has been relevant and provided the researcher with a unique in-depth involvement and understanding of the issues contributing to poor education in South Africa. The literature conducted in this study research exhibit that the interview schedule was the most suitable instrument to use to collect data for this research study. One of the findings in this research study is that the powers of administering schools are invested in School Governing Bodies (SGBs) and School Management Teams (STMs). Many parents in rural schools who form part of these bodies are not well-educated and can hardly make an informed decision to benefit learners. Therefore, the adoption of 4IR will centralise the education system and provide equal benefits to learners across the country. The adoption of 4IR on education will have a positive impact and enhance learners’ development in rural areas through robotics concepts. The findings of this research study show that the Department of Basic Education and the South African government are not ready for Fourth Industrial Revolution. However, iv there are signs for opportunities. The findings show the obstacles that can delay the adoption of 4IR to facilitate teaching and learning in rural public schools to bridge the gap that exist between rural public schools and private schools in the cities. The findings show that 4IR can transform the South African education system to compete with the world by producing scholars that are innovative and creative. The findings indicate how communities can transform through digital infrastructure developments to accommodate 4IR in learning in rural schools. This research study’s findings indicate ways in which the South
Thesis presented in partial fulfillment for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, University of the Witwatersrand, 2021
Keywords: 4th industrial revolution; Rural public schools; Teacher; Learners; Technology; Basic education; UCTD; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure